Media Komunikasi dan Kebutuhan Informasi Pariwisata Indonesia - Gayatri Atmadi; Nurul Robbi Sepang (Journal of Tourism and Creativity, 2018)
Abstract The aim of the research is to describe of communication media is able to fullfill the need of tourism information in Indonesia spesccialy for Jakarta worker. The result shows that on-line media is the best choice, because its characteristies is practice, easily to acces, and the information is actual. Detiktravel is on of the best choice media. The other social media are travelkompas.com and Inspirasi Perjalanan Yahoo Indonesia. The selection of digital media is important due to its simplicity and can encourage the Jakarta worker to use it. Time to access information more often at night (during at home) and use smartphone. Keyword: media communication, tourism information